The Nexus of Household Modernization and Socio-Economic Connectivity in Nepal: A 20-Year Principal Component and Canonical Correlation Analysis (2001-2021) - Prasad Sapkota, Ganga; Nain , Mohit (International Journal of Silkroad Institute of Research and Training, 2025)
Background: This study investigates the relationship between household welfare and socio-economic connectivity in Nepal over two decades (2001–2021). Understanding these dynamic interdependencies is crucial for effective infrastructure planning and equitable regional development in a context marked by rapid urbanization and persistent spatial inequalities. Method: The study analysed district-level census data from 2001 (n=75), 2011 (n=75), and 2021 (n=77). PCA was used to reduce two domains of variables: 27 household welfare indicators and 6 socio-economic connectivity indicators. These domain scores were then examined using CCA to assess their relationships. Significance was tested with Wilks’ Lambda, and redundancy indices measured how much variance each domain explained in other. Result: CCA revealed an exceptionally strong "modernization–connectivity" nexus (canonical R>0.92, p-value<0.01) across all decades, with digital infrastructure emerging as the primary driver by 2021. A secondary "migration–remittance" nexus (canonical R: 0.55–0.80) evolved from distress migration to an institutionalized remittance economy. Household characteristics explained 43–47% of connectivity variance, while connectivity explained only 17–19% of household variance, revealing significant asymmetry. Conclusion: Nepal exhibits a dual-structure economy comprising an "Urban–Modern Core" and a "Migrant–Remittance Periphery." Policy interventions must enhance digital infrastructure, formalize remittance channels, and prioritize basic services to promote inclusive development.